2016
DOI: 10.1093/mnras/stw144
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic alignments of BOSS LOWZ galaxies – II. Impact of shape measurement methods

Abstract: Measurements of intrinsic alignments of galaxy shapes with the large-scale density field, and the inferred intrinsic alignments model parameters, are sensitive to the shape measurement methods used. In this paper we measure the intrinsic alignments of the Sloan Digital Sky Survey-III (SDSS-III) Baryon Oscillation Spectroscopic Survey (BOSS) LOWZ galaxies using three different shape measurement methods (reGaussianization, isophotal, and de Vaucouleurs), identifying a variation in the inferred intrinsic alignmen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
85
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(93 citation statements)
references
References 91 publications
(165 reference statements)
7
85
1
Order By: Relevance
“…Comparing to other observations, Singh & Mandelbaum (2016) found, using low redshift luminous red galaxies, that alignment measurements with different shape estimators resulted in different inferred intrinsic alignment amplitudes. One of the possible reasons for this is that these shape estimators are sensitive to different galaxy scales.…”
Section: Global Intrinsic Alignmentscontrasting
confidence: 54%
See 2 more Smart Citations
“…Comparing to other observations, Singh & Mandelbaum (2016) found, using low redshift luminous red galaxies, that alignment measurements with different shape estimators resulted in different inferred intrinsic alignment amplitudes. One of the possible reasons for this is that these shape estimators are sensitive to different galaxy scales.…”
Section: Global Intrinsic Alignmentscontrasting
confidence: 54%
“…Such a dependence is expected due to the tidal nature of the phenomenon and has been seen in hydrodynamical simulations, where the alignment signal was stronger when the method used to define galaxy shapes up-weighted outer regions of galaxies (Velliscig et al 2015;Chisari et al 2015;Hilbert et al 2017). Observations have also hinted towards this, with Singh & Mandelbaum (2016); Huang et al (2018) looking into alignments as measured by different shape measurement methods and finding stronger alignments for methods more sensitive to the outer shape of a galaxy. In addition, Georgiou et al (2019) found that the alignment signal changes on small scales when shapes were measured from different broad band filters, with the change mostly sourced by satellite galaxies.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…So far, detections of this intrinsic alignment signal have largely been limited to bright, red galaxies (e.g. Mandelbaum et al 2006;Hirata et al 2007;Joachimi et al 2011;Blazek et al 2011;Singh & Mandelbaum 2016). It is possible that this contamination can be mitigated by removing these galaxies from the source sample, through improved photo-z methods, or with modelling approaches (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…before the effect of gravitational lensing on the observed shapes [see 1, 2, for reviews]. These are known to exist between luminous red galaxies at low redshift [3][4][5][6][7], and are considered a contaminant for cosmology with weak gravitational lensing [8][9][10]. Despite these alignments being measured to high significance in current galaxy surveys, there have been relatively few efforts on exploring possible models for this signal.…”
Section: Introductionmentioning
confidence: 99%